Preferential transcription of Paracoccidioides brasiliensis genes: host niche and time-dependent expression - Maristela Pereira; Alexandre Melo Bailão; Juliana Alves Parente; Clayton Luiz Borges; Silvia Maria Salem-Izacc; Célia Maria de Almeida Soares (Memorias do Instituto Oswaldo Cruz, 2009)
Paracoccidioides brasiliensis causes infection through inhalation by the host of airborne propagules from the mycelium phase of the fungus. This fungus reaches the lungs, differentiates into the yeast form and is then disseminated to virtually all parts of the body. Here we review the identification of differentially-expressed genes in host-interaction conditions. These genes were identified by analyzing expressed sequence tags (ESTs) from P. brasiliensis cDNA libraries. The P. brasiliensis was recovered from infected mouse liver as well as from fungal yeast cells incubated in human blood and plasma, mimicking fungal dissemination to organs and tissues and sites of infection with inflammation, respectively. In addition, ESTs from a cDNA library of P. brasiliensis mycelium undergoing the transition to yeast were previously analyzed. Together, these studies reveal significant changes in the expression of a number of genes of potential importance in the host-fungus interaction. In addition, the unique and divergent representation of transcripts when the cDNA libraries are compared suggests differential gene expression in response to specific niches in the host. This analysis of gene expression patterns provides details about host-pathogen interactions and peculiarities of sites within the host.